Introduction - Hvid, Helge (Nordic Journal of Working Life Studies, 2014)
The first article within this issue deals with the history of Swedish working life research. Carin Håkansta is the author of this interesting article. In the 1970s and 1980s, Sweden had an absolute dominance in the Nordic working life research, but from the mid-1990s, there was a gradual dismantling of the institutions that had carried the Swedish working life research. The most serious attack on the Swedish working life research came in 2007, when the National Institute for Working Life was closed down together with the Swedish Council for Working Life Research. A number of ‘Work Science’ departments at universities were established around 2000, but many of these institutions are now being integrated into larger institutions without any specific working life identity. The rise and fall of the Swedish working life research is associated with the rise and fall of the Swedish Social Democrats: as Håkansta points out, the strong public support to working life research in the 1970s and 1980s was linked to the Social Democrats' efforts to find a third way between capitalism and communism. The economy should be democratized, working life should be democratized and working life should be an arena for human development (...)